Economic Burden of Contraception Management in Spain - Inmaculada Parra Ribes; Juan José Rascón Poza; Ezequiel Pérez Campos; Ignacio Bugella Yudice; Maria Jesús Rodríguez Domingo (Journal of Health Economics and Outcomes Research)
**Background:** A wide variety of contraceptive methods are available, some of them reimbursed by the Spanish National Health System (SNHS). However, the number of unintended pregnancies (UP) is still significant, leading to a high economic burden, mainly derived from non-adherence to and the incorrect use of contraceptive methods.